Validity of a low-cost friction encoder for measuring velocity, force and power in flywheel exercise devices - Illera-Domínguez, V.; Fernández-Valdés, B.; Gisbert-Orozco, J.; Ramirez-Lopez, C.; Nuell, S.; González, J.; Weakley, J. (Biology of Sport, 2023)
The purpose of this study was to investigate the validity of a low-cost friction encoder against a criterion measure (strain gauge combined with a linear encoder) for assessing velocity, force and power in flywheel exercise devices. Ten young and physically active volunteers performed two sets of 14 maximal squats on a flywheel inertial device (YoYo Technology, Stockholm, Sweden) with five minutes rest between each set. Two different resistances were used (0.075 kg · m2 for the first set; 0.025 kg · m2 for the second). Mean velocity (Vrep), force (Frep) and power (Prep) for each repetition were assessed simultaneously via a friction encoder (Chronojump, Barcelona, Spain), and with a strain gauge combined with a linear encoder (MuscleLab 6000, Ergotest Technology, Porsgrunn, Norway). Results are displayed as (Mean [CI 90%]). Compared to criterion measures, mean bias for the practical measures of Vrep, Frep and Prep were moderate (-0.95 [-0.99 to -0.92]), small (0.53 [0.50 to 0.56]) and moderate (-0.68 [-0.71 to -0.65]) respectively. The typical error of estimate (TEE) was small for all three parameters; Vrep (0.23 [0.20 to 0.25]), Frep (0.20 [0.18 to 0.22]) and Prep (0.18 [0.16 to 0.20]). Correlations with MuscleLab were nearly perfect for all measures in all load configurations. Based on these findings, the friction encoder provides valid measures of velocity, force and power in flywheel exercise devices. However, as error did exist between measures, the same testing protocol should be used when assessing changes in these parameters over time, or when aiming to perform inter-individual comparisons.